Leaf epidermal features of lily boat (Rhoeo discolor (l'herit) hance) and wild daisy (Tridax procumbens L.) exposed to air pollutants. - Morin, Jay Sunday Sotomil
Apical and basal of Rhoeo discolor (1 Herit) hance and Tridax procumbens L. from a site which is relatively polluted with car exhaust pollutants (site A) and from a presumably relatively unpolluted site (site B) were compared in terms of four leaf epidermal features including (1) stomatal density, (2)stomatal width, (3) trichome density, and (4) trichome lenght. This was done to determine the changes in the leaf epidermal features of the plants exposed to air pollutants. Quantitative measurements and statistical analysis, using the Kruskal-Wallis H-test and the Turkey-Type Multiple Comparison, and the Two-Way Classification with Interaction and the t-test showed significant difference between plants from site A and site B. Stomatal density and stomatal width significantly changed for Rhoeo discolor, while stomatal density and trichome lenght significantly changed for Tridax procumbens. There was a signifcant difference in the stomatal density between the apical and basal for both plant species from both sites. A signifcant difference was observed in the trichome lenght of Tridax procumbens exposed to air pollutants.